An analysis of Talin methylation in leukocytes - Lim, Nicholas Kai Hung (2018)
As an integrin activator, Talin links the actin cytoskeleton of the migrating cell to membrane-bound integrin molecules, forming integrin-rich structures known as focal adhesions. Cell displacement is achieved by the resistance of actin retrograde flow by integrin-bound Talin1 in conjunction with actin polymerization-driven protrusions at the tip of the cell. Recently, our lab has shown that Enhancer of Zeste Homolog 2 (Ezh2)-mediated tri-methylation of Talin1 at Lys2454 (K2454me3) disrupts the binding of F-actin and promoting the turnover of focal adhesions. Since integrindependent migration is crucial to the recruitment of leukocytes, we aimed to determine the significance of K2454me3 in various immune cell types. Intriguingly, we observed an increase in the level of K2454me3 in infiltrated peritoneal neutrophils using the model of fMLF-induced peritonitis, suggesting a neutrophil activation-associated methylation of Talin1 in vivo. The increased abundance of K2454me3 in peritoneal neutrophils validated the physiological significance of Talin1 methylation. However, we did not observe an increase in K2454me3 in Jurkat T cells activated in vitro, which may have been caused by a lack of the Vav1-Ezh2-Talin1 complex; which is required for Talin methylation. Collectively, our data indicated a difference of a plausible cell type-specific complex formation between primary neutrophils and Jurkat T cells.